Inhibition of Pratylenchus penetrans by intercroping of Rudbeckia hirta and Lycopersicon esculentum in pot cultivation - Potter, J.W.; McKeown., A.W. (Phytoprotection, 2002)
In greenhouse pot culture over a 6-week period, population density of Pratylenchus penetrans declined pronouncedly both under Rudbeckia hirta alone and under a R. hirta - tomato combination, whereas tomato alone supported the nematode population. Population reduction is attributed in part to the known nematicidal effect of thiarubrine C in R. hirta. Overall, the presence of R. hirta in the tomato pot only slightly suppressed growth of either plant during the 6 weeks.